FAKTOR-FAKTOR YANG MEMPENGARUHI KEMANDIRIAN PETANIDALAM USAHATANI PADI ORGANIK DI KECAMATAN PAKEM KABUPATEN SLEMAN - , HARMOKO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Organic farming is one of the alternatives that are environmentally friendly farming systems. In addition to providing food safety, organic farming deliver widely to farmers to manage the farming by making use of resources. By implementing a system of organic farming through the rice farmers are expected to self- reliance. But not all farmers applying organic farming has had autonomy. This was caused by factors that originate from internal and external farmers. To explore this, the study aims: (1) know the number of farmers who have high autonomy, (2) determine the factors that affect the autonomy of farmers in organic paddy farming. This study uses descriptive and explanative. Site selection is done purposive selected Pakem District, with consideration of the region have demonstration plots of organic paddy in the certification process. Population and sample are organic farmers who cultivate paddy in the village and Pakembinangun Hargobinangun. Sampling was carried out by the census method. From the results obtained 48 census respondents. The results showed a high number of farmers with very low autonomy. Factors that affect the autonomy of farmers in organic paddy farming is self efficacy. While the motivating factors, the role of innovator agents, land and livestock ownership has no effect. Variables local knowledge to give real effect in organic paddy farming. Local knowledge in the form of knowledge in planting. This knowledge is the technical land management, maintaining soil fertility, natural resource use and knowledge of farmers about pranatamangsa.